Normalization of diabetic wound healing - Francis-Goforth, Kellie N. (2009)
Impaired wound healing in diabetics is due to pathological angiogenesis, which is a result of aberrant sphingosine-1-phosphate (S1P) signaling. Pharmacological modulation of sphingosine-1-phosphate-dependent signaling normalizes healing in diabetic wounds.